SCIENTIFIC STYLE OF THINKING IN THE STRUCTURE OF PRE-FUNDAMENTAL KNOWLEDGE - Синяков, С. В.; Сластенко, Е. Ф. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article deals with the peculiarities of realization of scientific style thinking in historical research.